Influence of intermediary filling material on microleakage of intracoronally bleached and restored teeth - Maryam Khoroushi; Atieh Feiz; Maysam Ebadi (Wolters Kluwer Medknow Publications, 2009)
Background: Failure of composite restorations in terms of microleakage after intracoronal bleaching has been reported. The purpose of this study was to assess in vitro effect of sodium ascorbate and calcium hydroxide as intermediary filling materials to repair the microleakage associated with adhe-sive restoration following intracoronal bleaching. Methods: Sixty endodontically-treated incisors with access cavities extended to the cementoenamel junction in gingival margin were randomly divided into five equal groups. In group 1, cavities were restored by applying Single Bond and Z100 composite resin. In groups 2-5, 35% hydrogen peroxide gel was placed into the pulp chamber and sealed for 5 days. In group 2, teeth were then restored as in group 1. In groups 3 and 4, 10% sodium ascorbate gel and calcium hydroxide paste were applied in the pulp chamber for 40 hours, removed, rinsed and then, restored. In group 5, the cavities were incu-bated for 7 days and then, restored. Samples were thermocycled, immersed in basic fuschin, and sec-tioned. Dye penetration was scored using a stereomicroscope. Data were analyzed using Kruskal- Wallis and Mann-Whitney U tests (α = 0.05). Results: There was no significant difference in enamel margins (P = 0.163). In dentinal margins (P = 0.003), groups 1, 3 and 5 exhibited similar leakage patterns, each one of groups 1, 3 and 5 had sig-nificant differences with each one of groups 2 and 4. Conclusion: Intracoronal bleaching using 35% H2O2 gel increases the microleakage in dentinal margins. Application of the antioxidant agent or a seven-day delay following bleaching may improve the marginal integrity. Applying calcium hydroxide might jeopardize dentinal sealing.